Investigating the Impact of Entrepreneurship Education, Entrepreneurship Experience, and Entrepreneurship Intention among Business Education Undergraduates in Tertiary Institutions in Rivers State - Bara, Imaobong Ignatius; Ahiakwo Ufuoma Perpetual (Research Parks Publishers, 2026)
The study examined the impact of entrepreneurship education and the entrepreneur experience and intentions of undergraduate of business education in tertiary institutions in Rivers State. Two research questions and two corresponding hypothesis guided the study. A Survey research design was used for the study. The study population comprised of all undergraduates students of business education in three universities in Rivers State, namely: University of Port Harcourt, Rivers State University and Ignatius Ajuru University of Education. A sample of 180 study participants were selected through simple random and proportional techniques. A self designed instrument titled: Entrepreneurship Education, Experience and Intentions (E.E.E.E.I.) was used for data collection. The instrument was validated by experts from the department of business Education, Ignatius Ajuru University of Education. A reliable coefficient index of 0.874 was obtained using Cronbach Alpha statistics, mean and standard deviation and independent t-test were used to analyze the descriptive and inferential statistics. Major findings of the study revealed a strong and significant influence between Entrepreneurship Education and Entrepreneurship Experience and Intentions. It was however, recommended that government should adequately fund entrepreneurship education.